WILLINGNESS TO COMMUNICATE (WTC) AMONG TERTIARY ENGLISH EDUCATION STUDENTS: A SURVEY STUDY (ELT Echo : The Journal of English Language Teaching in Foreign Language Context, 2022)
Most of the research under the topic of Willingness to Communicate (WTC) was mostly found in the context of speaking outside the classroom and in everyday communication. Therefore, the researchers conducted a study on WTC among English Education students which focused on the classroom context. This is a survey study which is quantitative in nature. This study used the instrument from Khatib and Nourzadeh (2014). To obtain the data, questionnaires were distributed to students majoring in the English Education department. 169 students were involved in this study. The data then were analyzed by using descriptive statistics from SPSS. The results revealed that overall, the biggest reason for students' willingness to communicate is learning responsibility (M=4.06) while the lowest reason is the context of using English (M=3.77). Specifically, students are willing to communicate in several circumstances, such as: 1) students are more likely to want to talk when in group work; 2) students were more willing to speak when they discussed English and Indonesian culture as a group; 3) students will be willing to speak when it involves personal experience; 4) students prefer to talk about films and series rather than talking about sports; 5) students were more willing to ask their classmates about the correct pronunciation of a word than to raise their hands to ask the teacher; and 6) students are more willing to talk to students sitting next to them before the lecturer enters class than to talk to foreign students from other classes.